Improving Students' Vocabulary Mastery Through Climbing Up A Ladder Game - Annisa Juliani; Ika Handayani; Yudi Juniardi (Jurnal Langua, 2023)
Researcher described that climbing up a ladder game could be effect to increase vocabulary. The participant was eighth class in SMPN 5 Cilegon. The researcher applied CAR method which consisted two cycles and two meetings per cycle. Pre-test and post-test were used collecting quantitative data, coupled with observation sheet and documentation collect qualitative data. Climbing up a ladder game could increase the students’ motivation, improve their vocabulary mastery, and establish the class to be more active. The researcher used pretest before applying the game and the posttest after that to measure their ability. The result of pretest showed that the average score was 68,00. Then the result of posttest 1 (cycle 1) was 77,69 and the result of post-test 2 (cycle 2) was 83,58. The researcher found out improvement in vocabulary on the other hand students passed score in school after being given the climbing up a ladder game. It can be concluded that students’ vocabulary mastery could be improved by climbing up a ladder game.